KEPEMILIKAN MANAJERIAL & KOMISARIS INDEPENDEN SEBAGAI PEMODERASI KINERJA LINGKUNGAN DAN CSR TERHADAP KINERJA KEUANGAN - Cameline Limanto; Jesica Handoko (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2022)
This study aims to test and analyze the influence of environmental performance and corporate social responsibility on the company's financial performance with corporate governance as moderation. Environmental performance is measured using PROPER ratings, financial performance is measured using return on equity, and return on sales, as well as corporate governance that is proxies with managerial ownership and independent commissioners. The research object used is a mining company registered in the Indonesia stock exchange period 2015-2019. Purposive sampling techniques and multiple linear data analysis techniques were used to obtain samples as well as to test hypotheses in this study. The results of this study showed that environmental performance has a significant positive effect on financial performance, while corporate social responsibility has no effect on financial performance, managerial ownership is not able to moderate the relationship of environmental performance to financial performance and independent commissioners are able to moderate the relationship of environmental performance and corporate social responsibility to financial performance.